Evoluç\~ao do gasto com medicamentos do sistema único de saúde no período de 2010 a 2016 - Fabiola Sulpino Vieira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– The objective of this text is to present and address the spending on medicines of the Brazilian Public Health System (SUS) from 2010 to 2016 in a budgetary perspective. The analysis was based on the budget execution of the Ministry of Health and the health departments of the states, the Federal District and the municipalities, using data from two publicly available information systems, Siga Brasil and Siops. SUS spending on medicines rose from R 14.3 billion in 2010 to almost R 20 billion in 2015 (growth of 40%), falling to R 18.6 billion in 2016 (-7% in the last two years), in real terms, as a probable consequence of the economic crisis on these expenditures of subnational entities and greater role of the Ministry of Health to the medicines procurement and financing, including the Farmácia Popular Program. Between 2010 and 2016, SUS expenses with medicines registered growth of 30%. There was a significant increase in drug spending in the last seven years, with a special effort by the Ministry of Health, which started directly to execute the largest portion of the its budget for the purchase of these products. The Specialized and Strategic Components, as well as the Farmácia Popular Program, are very important for this increase. The incorporation of new medicines and the increase in lawsuits on pharmaceuticals may be driven the drug spending. The share of federal spending on pharmaceuticals in public health care spending rose from 11 percent in 2010 to 16 percent in 2016. The rising trend and the factors that drive higher spending can increase the drug spending which can compromise more significant portions of the Ministry of Health budget. That may reduce the availability of resources for the supply of other health goods and services to the population, because the federal budget is limited until 2036 by the Constitutional Amendment 95, approved in 2016.
Keywords: H51; H60; I18; 330; drug costs; health expenditures; budgets; Unified Health System